ChemInform Abstract: Asymmetric [3 + 2] Cycloaddition of Donor—Acceptor Aziridines with Aldehydes via Carbon—Carbon Bond Cleavage. Issue 42 (September 2016) - Liao, Yuting; Liu, Xiaohua; Zhang, Yu; Xu, Yali; Xia, Yong; Lin, Lili; Feng, Xiaoming
Abstract: The protocol allows for the preparation of a broad range of cis‐1, 3‐oxazolidines in high yields and with high enantiomeric excesses.